Analisis Regresi Pengaruh Motivasi, Disiplin Kerja, dan Lingkungan Kerja terhadap Kinerja Pegawai di Dinas Pendidikan dan Kebudayaan Kota Jayapura - Laela Tambawang; Susilawaty; Yuliati Kalapadang; Wa Ode Alya (MUTIARA: Jurnal Ilmiah Multidisiplin Indonesia, 2026)
Employee performance is a crucial factor in supporting the success of government organizations in achieving public service objectives. The Department of Education and Culture of Jayapura City continues to face various challenges related to work motivation, work discipline, and the work environment, which are presumed to influence employee performance. This study aims to analyze the effects of work motivation, work discipline, and the work environment on employee performance, both partially and simultaneously. The research employed a quantitative approach with an explanatory research design. The study population consisted of 87 employees, all of whom were selected as respondents through a saturated sampling technique. Data were collected using questionnaires and analyzed through multiple linear regression with the assistance of IBM SPSS Statistics. The findings reveal that work motivation has a positive and significant effect on employee performance, with a significance value of 0.002 and a regression coefficient of 0.388. Work discipline also demonstrates a positive and significant effect, with a significance value of 0.002 and a regression coefficient of 0.310. The work environment emerges as the most dominant variable, with a significance value of 0.000, a regression coefficient of 1.238, and a beta coefficient of 0.417. Simultaneously, work motivation, work discipline, and the work environment significantly influence employee performance, as indicated by an F-statistic of 40.438 and a significance value of 0.000. The coefficient of determination (R Square) of 0.594 indicates that 59.4% of the variation in employee performance can be explained by these three variables. The novelty of this study lies in its empirical evidence that the work environment constitutes the most dominant factor affecting employee performance within the Department of Education and Culture of Jayapura City, an institution characterized by distinctive organizational features and service-area conditions.